2017
DOI: 10.2217/pgs-2017-0117
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Breast Cancer and the Potential for Targeted Therapy

Abstract: Breast cancer is composed of several well-recognized subtypes including estrogen receptor, progesterone receptor and HER2 triple-negative breast cancer (TNBC). Without available targeted therapy options, standard of care for TNBC remains chemotherapy. It is of interest to note that TNBC tumors generally have better responses to chemotherapy compared with other subtypes. However, patients without complete response account for approximately 80% of TNBC. Mounting evidence suggests significant heterogeneity within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
142
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 99 publications
(110 reference statements)
1
142
0
1
Order By: Relevance
“…Targeted radioimmunoimaging with monoclonal antibody has been considered a successful imaging for many kinds of cancer . Radiolabelled 125 I‐antiTLR5 mAb may provide a method for visualizing TLR5 expression in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Targeted radioimmunoimaging with monoclonal antibody has been considered a successful imaging for many kinds of cancer . Radiolabelled 125 I‐antiTLR5 mAb may provide a method for visualizing TLR5 expression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted radioimmunoimaging with monoclonal antibody has been considered a successful imaging for many kinds of cancer. 10 Radiolabelled 125 I-antiTLR5 mAb may provide a method for visualizing TLR5 expression in vivo. Our data suggested that 125 I-antiTLR5 mAb could be used in these TNBC tumour models, which is more clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite improved treatment options using therapeutic monoclonal antibodies against HER2, the acquisition of drug resistance remains a major problem and could lead to tumour recurrence . For triple negative carcinomas, no targeted therapy is available . HER2 overexpression in human breast cancer indicates a risk of recurrence independent of whether the axillary node is positive or negative for micrometastases .…”
Section: Introductionmentioning
confidence: 99%